When emotion meets reason: the development and validation of EpiCT-CI scale to measure epistemic emotions in critical thinking application and cultural identity constructions - Peng, Yue (Frontiers in Psychology, 2025)
IntroductionEpistemic emotion is a significant concept in education, but traditional scales rarely focus on the status of epistemic emotions in intercultural issues. Additionally, cultural identity and critical thinking are vital in navigating the complexities inherent in intercultural contexts. Existing measures of critical thinking and cultural identity seldom consider the influence of emotions. The EpiCT-CI Scale, developed in this research, seeks to bridge this gap by measuring how epistemic emotions influence critical thinking and cultural identity in intercultural settings.MethodDeveloping and validating the EpiCT-CI Scale combines qualitative and quantitative methods. Study 1 collected data from students’ comments, judgments, and narrations about critical thinking during COVID-19. Study 2 focused on the emotional experiences of constructing cultural identity by reading, analyzing, and writing about cultural issues. The data from Studies 1 and 2 are analyzed in NVivo 15.0. The original EpiCT-CI Scale is validated through SPSS 20.0 and Amos 29.0 in Study 3.ResultsThe results from Studies 1 and 2 indicate that epistemic emotions are a blend of neutral, positive, and negative states, rather than simple linear progressions. The initial 52-item scale underwent a thorough evaluation, modification, and validation process in Study 3, resulting in a four-dimensional 19-item EpiCT-CI Scale, which represents four groups of epistemic emotions: joy in critical cultural inquiry, boredom in critical cultural reflection, curiosity in cultural identity reflection, and distress in cultural adaptation. The EpiCT-CI Scale provides an effective tool for assessing epistemic emotions in cultural identity constructions and critical thinking applications.